Clinical Course of SARS-CoV-2 Infection in Adults with ESKD Receiving Outpatient Hemodialysis. Issue 12 (30th December 2021) - Bardossy, Ana Cecilia; Korhonen, Lauren; Schatzman, Sabrina; Gable, Paige; Herzig, Carolyn; Brown, Nicole E.; Beshearse, Elizabeth; Varela, Kate; Sabour, Sarah; Lyons, Amanda K.; Overton, Rahsaan; Hudson, Matthew; et al.
Visual Abstract: Abstract : Key Points: Patients with ESKD on dialysis had persistent and intermittently positive RT-PCR tests for severe acute respiratory syndrome coronavirus 2. Evidence for presence of infectious virus was lacking in most cases. A symptom-based approach, instead of a test-based approach, should be used to decide when to discontinue transmission-based precautions. Background: Patients with ESKD on maintenance dialysis receive dialysis in common spaces with other patients and have a higher risk of severe SARS-CoV-2 infections. They may have persistently or intermittently positive SARS-CoV-2 RT-PCR tests after infection. We describe the clinical course of SARS-CoV-2 infection and the serologic response in a convenience sample of patients with ESKD to understand the duration of infectivity. Methods: From August to November 2020, we enrolled patients on maintenance dialysis with SARS-CoV-2 infections from outpatient dialysis facilities in Atlanta, Georgia. We followed participants for approximately 42 days. We assessed COVID-19 symptoms and collected specimens. Oropharyngeal (OP), anterior nasal (AN), and saliva (SA) specimens were tested for the presence of SARS-CoV-2 RNA, using RT-PCR, and sent for viral culture. Serology, including neutralizing antibodies, was measured in blood specimens. Results: Fifteen participants, with a median age of 58 (range, 37‒77) years, were enrolled. Median duration of RT-PCR positivity from diagnosis was 18 days (interquartile range [IQR], 8‒24 days). Ten participants had at least one, for a total of 41, positive RT-PCR specimens ≥10 days after symptoms onset. Of these 41 specimens, 21 underwent viral culture; one (5%) was positive 14 days after symptom onset. Thirteen participants developed SARS-CoV-2–specific antibodies, 11 of which included neutralizing antibodies. RT-PCRs remained positive after seroconversion in eight participants and after detection of neutralizing antibodies in four participants; however, all of these samples were culture negative. Conclusions: Patients with ESKD on maintenance dialysis remained persistently and intermittently SARS-CoV-2–RT-PCR positive. However, of the 15 participants, only one had infectious virus, on day 14 after symptom onset. Most participants mounted an antibody response, including neutralizing antibodies. Participants continued having RT-PCR–positive results in the presence of SARS-CoV-2–specific antibodies, but without replication-competent virus detected.